Escola território e violência : reflexos no campo escolar - Delgado, Marceli Maria dos Santos (2014)
Violence in schools is a problem and this has worried the people who live together in the school grounds; it is an obstacle that impairs social relations and mediation of scientific knowledge. This work aims to identify the episodes of violence that arise within the school and its surroundings, and how they reflect on the school field of Maringa State Public Institutions; called North, South and Central regions. Reasoned by means of literature and information gathered by the use of field research; as well as questionnaires given to students and teachers where it asks about the relationship of living in this community, instances of violence and the impact of these actions on the lives of social actors. The considerations of the different questions directed at students and teachers have the pretension to collect answers to questions about the researcher, which is school violence, violence which the main focus in the school field and how this practice of violence affects school stakeholders. In possession of listed results we intend to present to the school communities that serve to support the development of public policies that reduce school violence and consequently improve the quality of education in Paraná State Schools. After compiling the data, it appears that the main violence to seize territory in the opinion of school teachers are poor physical structure of two institutions, the lack of adequate to meet the special needs instruments, vandalism, assaults physical between students, bullying, theft, robbery and threats, as well as illicit substances that enter the school, fear of traffickers, gangs, school grounds and invasion by strangers; and the opinion about the presence of the school patrol. Understanding of learners towards violence are, a deficiency of computer classes, the lack of public policies for young people in a different time of school, problems of building infrastructure, theft, robbery, assault, insults, bullying, threats, insecurity, verbal aggression, predation public property, possession of weapons on school territory among other violent actions that are in evidence in the present work.